Pemungutan Khrom Dari Limbah Penyamakan Kulit Dengan Kapur Padam Secara Sinambung Ditinjau Dari Segi Kinetika - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Tanning process using chromic sulphate solution produces liquid waste having a high chromic ion concentration (1500-5000 mg/L), The allowable concentration of chromium in liquid waste is 2 mg/L. One of the possible reactants which could be used to recover chromium from tanning waste water is hydrated lime. The reaction between hydrated lime and chromic ion was carried out in an upright reactor provided with serrated slanted baffles. The chromium content of the samples taken at steady state condition was determined using Atomic Absorption Spectrophotometer (AAS). The variables studied were air flow rate, temperature, and reactants molar ratio. The results showed that the rate of reaction was controlled by mass transfer. The relation between mass transfer constant and air flow rate could be expressed as : kL=1,036 (10 -3) G "127 In the temperature range of 300 K to 320 K, the chemical reaction rate constant followed Arrhenius equation, while temperature had a tiny effect on the diffusivity at the product layer. The effect of temperature on the chemical reaction rate constant and diffusivity were given by 879,6449 kR = 0,8594 e RT and 878,8501 De = 1,0829(10-i) e AT The molar ratio of hydrated lime and chromic ion did not affect the mass tranfer constant, diffusivity, and chemical reaction rate constant significantly.